Design of a multiplex PCR assay for the simultaneous detection and confirmation of Neisseria gonorrhoeae. Issue 5 (1st April 2010) - O'Callaghan, Isabelle; Corcoran, Daniel; Lucey, Brigid
Abstract : Objectives: To improve the detection of Neisseria gonorrhoeae by designing a multiplex PCR assay using two N gonorrhoeae -specific genes as targets, thereby providing detection and confirmation of a positive result simultaneously. Methods: PCR primers were designed to detect two N gonorrhoeae genes, namely porA and pgi1. Primers for an internal control targeting the ompW gene of Vibrio cholerae were also designed and incorporated in the assay. The DNA of 45 clinical isolates including 33 N gonorrhoeae isolates, seven non-gonococcal Neisseria species, and five non-Neisseria species was tested using the multiplex PCR assay. Results: All 33 N gonorrhoeae isolates were successfully detected by the assay and none of the non-gonococcal isolates was detected. The assay showed a sensitivity and specificity of 100%, and a limit of detection of 1.25 ng of DNA. Conclusion: This multiplex PCR assay offers a sensitive and specific assay suitable for the detection of N gonorrhoeae, and offers real potential for diagnostic use.